Urban Sustainability in Arctic Cities: Challenges and Opportunities of Implementing the Sustainable Development Goals - Soroudi, Ava; Rizzo, Agatino; Ma, Jing (Cogitatio Press, 2024)
Arctic cities are at the forefront of climate change, experiencing distinctive obstacles in their endeavors to pursue green transitions and attain sustainability objectives. These cities are marked by high energy consumption, primarily driven by activities related to resource extraction and the demanding climate. Moreover, they rely heavily on natural resources for growth, have limited infrastructure, and experience significant external and internal remoteness. This article presents a comprehensive analysis of urban sustainability in Arctic cities, focusing on key themes, trends, and challenges. Through a systematic review of extant literature, this study examines current research on urban sustainability in the Arctic and identifies crucial gaps, delineating a path to sustainability. Using VOSviewer software, six thematic clusters were identified: climate change and environmental adaptation, SDGs and smart urban planning, sustainable development and urban governance, sustainable economic development, social sustainability, and green energy transition. These clusters provide valuable insights into the dominant themes and evolving discourse in Arctic sustainability research. The findings show that the literature focuses predominantly on Russian Arctic cities, signaling an imperative for a more inclusive strategy encompassing a broader spectrum of Arctic cities. Additionally, sustainability is inherently site-specific and necessitates a nuanced understanding that incorporates different stakeholders’ perspectives and considers particular regional traits to create a more effective and meaningful approach to measuring and achieving sustainability in Arctic cities. This article contributes to the ongoing discourse on sustainability in Arctic cities by advocating for a comprehensive framework that accommodates unique challenges and opportunities of Arctic urban environments.